Feeding Revolution: The Black Panther Party and the Politics of Food - Potorti, Mary (Radical Teacher, 2014)
This chapter examines the role of food in the symbolic politics and practical agenda of the Black Panther Party (BPP), founded in the late 1960s in Oakland, California. Situating hunger and the politics of food at the center of drives for racial justice, it argues that the BPP’s anti-hunger efforts and food-centered campaigns were driven by an implicit understanding of the power of food in battles over racialized definitions of personhood, a forum for both enforcing and resisting hegemonic authority. From this vantage, the Panthers and their allies in the East Bay community utilized the Party’s popular food programs, specifically its Free Breakfast for School Children Program, as staging grounds to prepare for a revolutionary overthrow of the socio-economic order. In addition to strengthening the physical bodies of African Americans to ensure their “survival pending revolution,” the food programs served a deeper organizing function by encouraging community members to come together to meet an immediate, practical need and, in doing so, to visualize themselves as part of a larger movement for change. The Panthers’ subsequent demands for consumer rights and calls for conscientious consumption (both as purchasers and eaters of food) highlighted the role of food politics in perpetuating racial injustice while demonstrating the capacity for food-related protest to challenge structures of hunger and patterns of widespread malnourishment.